Electric field control of chiral magnetic domains in the high-temperature multiferroic CuO - Babkevich, P; Poole, A; Johnson, R; Roessli, B; Prabhakaran, D; Boothroyd, A (2012)
We have studied the high temperature multiferroic cupric oxide using polarized neutron diffraction as a function of temperature and applied electric field. We find that the chiral domain population can be varied using an external electric field applied along the b axis. Using representation analysis we derive the incommensurate magnetic structure in the multiferroic phase. The origin of the magnetoelectric coupling is consistent with models based on the inverse Dzyaloshinskii-Moriya interaction, but is different from the simple cycloidal mechanism.